Sodium azide as a catalyst for the hydration of nitriles to primary amides in water. (1st May 2015) - Bahrami, Kiumars; Khodaei, Mohammad Mehdi; Roostaei, Mohsen
The selective conversion of aromatic nitriles to primary amides has been accomplished using sodium azide. The corresponding amides were obtained efficiently in excellent yields. This reaction was carried out under eco-friendly conditions using water in the absence of organic solvents.